ASP.NET 2.0 web parts in action : building dynamic web portals - Neimke, Darren (Manning, 2007)
"A must-buy for every ASP.NET developer using Web Parts." Scott Guthrie General Manager Microsoft Developer Division "Squeezes the full potential out of ASP.NET Web Parts." Andres Sanabria Lead Program Manager ASP.NET and Server Application Frameworks Using Web Parts, ASP.NET developers can create portals with the same advanced features found in sites such as Live.com and Google ig. ASP.NET 2.0 Web Parts in Action demystifies portal design, development, maintenance, and deployment. In over 400 code-packed pages, ASP.NET expert Darren Neimke shares his deep understanding of the controls and services that make up the portal framework. This book will help you to code like a guru but think like a user. For example, you'll discover how to use Web Parts to reduce four-step actions to a single click with a strategically-placed edit button. Learn to balance features and usability to make your portals both look good and work well. ASP.NET 2.0 Web Parts in Action gives you the tools you need to move your ideas off the whiteboard and bring them to life. Find out how to provide the personalization options your users want while preserving the look and feel of your portals with solid designs and custom chrome. Create usable information dashboards and tackle tough interoperability questions with confidence. All the information in this book is performance-tested. Author Darren Neimke walks you through Web Parts concepts including static and dynamic connections, WebPartManager, SQLPersonalizationProvider, and the hot new ASP.NET Atlas framework. Whether you're creating custom solutions or adding Web Parts to SharePoint 2007, exploring Atlas or dabbling in gadgets, ASP.NET 2.0 Web Parts in Action will get you started and guide you as you build successful portals using ASP.NET Web Parts